Community Entrepreneurship in Deprived Neighbourhoods: Comparing UK Community Enterprises with US Community Development Corporations - David P. Varady; Reinout Kleinhans; Maarten van Ham (Institute for the Study of Labor (IZA), 2015)
Through a review of the recent American community development literature, this paper tests the assertion that British community enterprises (CEs) are fundamentally similar to American community development corporations (CDCs), and therefore, that CEs can learn from CDCs. In the context of the current austerity regimes, CEs and community entrepreneurship are increasingly considered as a means to continue small-scale urban regeneration, not only in the UK but also in several other European countries. While the CDC sector has achieved a relatively successful record in affordable housing production in distressed areas, CDCs are fundamentally limited in terms of reversing the processes of community decline. Our comparison of CDCs and CEs reveals similarities, but also differences with regard to organizational characteristics, co-operation on multiple scales, comprehensiveness, targeting and community participation. Apart from outlining lessons that CEs can learn from CDS, we provide recommendations for further research that should cover the lack of empirical evidence in this field.
Keywords: L26; L31; R23; 330; community development corporations; community enterprises; neighborhood revitalization; entrepreneurship; regeneration; United States; United Kingdom